Lippincott manual of nursing practice - Nettina, Sandra M.; Ovid Technologies, Inc. (Philadelphia : Wolters Kluwer, 2019)
'A classic text since it was first published in 1974, the Lippincott Manual for Nursing Practice has provided essential nursing knowledge and up-to-date information on patient care for nearly 40 years. Organized into five major parts, covering the Nursing Process and Practice; Medical-Surgical Nursing; Maternity & Neonatal Nursing; Pediatric Nursing; and Psychiatric Nursing. Written in an easy-to-read outline format, content is evidence-based and filled with procedure guidelines, Nursing Care Plans, Patient Education boxes, Standards of Care, and Assessments'--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nursing Care; Handbooks; Nursing -- Handbooks, manuals, etc